Examining emotion-, personality-, and reward-related dispositional tendencies in relation to eating pathology and weight change over seven years in the Longitudinal Assessment of Bariatric Surgery (LABS) study. (January 2020) - Lavender, Jason M.; King, Wendy C.; Kalarchian, Melissa A.; Devlin, Michael J.; Hinerman, Amanda; Gunstad, John; Marcus, Marsha D.; Mitchell, James E.
Abstract: This study examined dispositional emotion-, personality/temperament-, and reward-related variables in relation to post-surgery eating pathology and weight-change among 107 adults who underwent Roux-en-Y gastric bypass (RYGB) or laparoscopic adjustable gastric banding (LAGB). As part of a prospective cohort study, annual post-surgical assessments were conducted to evaluate eating pathology, using the Eating Disorder Examination-Bariatric Surgery Version, and percent weight change from pre-surgery. Dispositional measures were administered at the 6- or 7-year assessment and included the Affect Intensity Measure, Difficulties in Emotion Regulation Scale, UPPS-P Impulsive Behavior Scale, Adult Temperament Questionnaire-Effortful Control Scale, and Sensitivity to Punishment/Sensitivity to Reward Questionnaire. Results from a series of linear mixed models revealed significant associations of emotion dysregulation, affect intensity, positive and negative urgency, effortful control, and reward sensitivity with eating pathology severity across 7 years; additionally, all but two of the subscales comprising the total scores were also significantly associated. Fewer statistically significant results were found in relation to weight change; emotion dysregulation and affect intensity (along with several subscales) were significantly associated with lower percent weight change (i.e., less weight loss), but of the reward-related and personality/temperament variables, only total effortful control emerged as significant. However, the associations of the other variables with both outcomes were consistently in the expected direction. Associations also appeared consistent across surgical procedures. Taken together, findings suggest that certain dispositional tendencies may relate to less optimal long-term outcomes following bariatric surgery and thus may be useful to assess in pre-surgical or early post-surgical evaluations to inform targeted recommendations. Highlights: Dispositional variables may be associated with bariatric surgery outcomes. Emotion, personality, and reward variables related to eating pathology over 7 years. Primarily emotion variables related to post-surgical weight change over 7 years. Pre-surgical or early post-surgical assessments of these constructs may be useful.